An Error Analysis on Students’ Composition of Descriptive Text at the Tenth Graders of Sman 3 Bangkalan, Madura - Aditya, Maulana Yusuf (Penerbit STKIP PGRI Bangkalan, 2017)
As one of language skill, writing should be mastered by students. But in fact, a number of them especially pre university students still feel difficulty in it. So, in the sequence of efforts to minimize the errors, this study offers one of valuable ways called error analysis. The present study deals primarily with the result of students’ composition by the tenth graders of SMAN 3 Bangkalan, focused on the use of simple present tense in descriptive text and ungrammaticality found in it. The aim of this research are to find out the types of errors and the causes of errors. This research used descriptive qualitative method and data collection technique was documentation. Documentation data had shown that they made diverse errors in their composition. The research instrument was students’ worksheet then the researcher analyzed the students’ errors. Content analysis is a technique to analyze the data. The result of this research was found that the greatest number of errors was overgeneralization (OG). The students apllied a structure that they had already experienced in another new situation. Most of the students made errors caused by intralingual transfer. It means that the first language has influenced them in making composition. Looking at these results, students are not expected to be hopeless in learning English. They must study harder than before by asking their teachers some concepts. Meanwhile, the teachers should apply an appropriate and effective method of errors correction. For the readers, they can learn from the students of this research in order to they do not make the same errors